2021
DOI: 10.1101/2021.12.23.474027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological blockade of muscle afferents and perception of effort: a systematic review with meta-analysis

Abstract: The perception of effort (PE) provides information on task difficulty and influences physical exercise regulation and human behavior. This perception differs from other-exercise related perceptions such as pain. There is no consensus on the role of group III-IV muscle afferents as a signal processed by the brain to generate PE. The aim of this meta-analysis was to investigate the effect of pharmacologically blocking muscle afferents on the PE. Six databases were searched to identify studies measuring the ratin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 138 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…These studies have shown that, when the feeling of effort is measured separately from other performance-related feelings, reports of sensations of effort increase as physical exertion increases even when afferent signals are blocked (Bergevin et al, 2021). Evidence of this kind tips the scale in favor of centralism.…”
Section: Peripheralism Vs Centralismmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that, when the feeling of effort is measured separately from other performance-related feelings, reports of sensations of effort increase as physical exertion increases even when afferent signals are blocked (Bergevin et al, 2021). Evidence of this kind tips the scale in favor of centralism.…”
Section: Peripheralism Vs Centralismmentioning
confidence: 99%
“…Empirically, recent research used epidural anesthesia to block afferent signals from the muscles to the nervous system while participants perform effortful physical activities. These studies have shown that, when the feeling of effort is measured separately from other performance‐related feelings, reports of sensations of effort increase as physical exertion increases even when afferent signals are blocked (Bergevin et al., 2021). Evidence of this kind tips the scale in favor of centralism.…”
Section: Theories Of the Feeling Of Effortmentioning
confidence: 99%
“…3 FBE-Metabolic and similar views are susceptible to a serious objection: afferent signals are neither sufficient nor necessary for FBE. They are not sufficient, since the addition of lactate and metabolites in the blood (characteristic byproducts of the metabolic processes involved in muscular exertion) generates feelings of muscle fatigue and pain, but not feelings of effort (Pollak, Swenson, et al 2014;Pageaux and Gaveau 2016;Bergevin, Steele, et al 2021). Distinguishing effort from fatigue is important: feelings of fatigue involve a sense of tiredness or heaviness, and are associated 3 There is a long-standing debate between peripheralists and centralists (according to which the feeling of effort arises from commands originating in the central nervous system, identifiable with commands of the will).…”
Section: Fbe: the Problem With Metabolic Accountsmentioning
confidence: 99%